PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA DAN MASA KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN PT PLN (PERSERO) UP3 LAHAT - Thoriq Kusumo; Juhaini Alie (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Employee performance is a key factor in achieving organizational goals and is influenced by human resource quality, including educational level, work experience, and length of service. This study aimed to examine the effects of these variables on employee performance at PT PLN (Persero) UP3 Lahat. A quantitative approach with descriptive and verificative methods was employed involving 99 employees selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 25. The results indicate that educational level, work experience, and length of service have a positive and significant effect on employee performance, both partially and simultaneously, with educational level being the most dominant variable. The study concludes that improving human resource quality through education, work experience, and length of service contributes to enhanced employee performance.